Actinomycosis of the ankle joint - Ramachandra, Sunitha; Kuruvila, Sarah; CK, John (Annals of Pathology and Laboratory Medicine, 2014)
We report a case of actinomycosis of the ankle joint with synovial involvement which resisted the usual treatment. Actinomycotic infection of the extremities involving the bone and joints is rare. After the initial diagnosis, our case was treated with ampicillin for six months with no benefit. Instead the condition worsened with the development of tiny pockets of fluid collections within the soft tissue and increased inflammation. Surgical debridement was done to drain the fluid collections and the patient was treated with combined regimen of Cotrimoxazole and Rifampicin with good response clinically and radiologically. Timely intervention and the correct diagnosis saved the limb.